Vagal tone during infant contingency learning and its disruption. Issue 3 (30th October 2015) - Sullivan, Margaret Wolan
ABSTRACT: This study used contingency learning to examine changes in infants' vagal tone during learning and its disruption. The heart rate of 160 five‐month‐old infants was recorded continuously during the first of two training sessions as they experienced an audiovisual event contingent on their pulling. Maternal reports of infant temperament were also collected. Baseline vagal tone, a measure of parasympathetic regulation of the heart, was related to vagal levels during the infants' contingency learning session, but not to their learner status. Vagal tone levels did not vary significantly over session minutes. Instead, vagal tone levels were a function of both individual differences in learner status and infant soothability. Vagal levels of infants who learned in the initial session were similar regardless of their soothability; however, vagal levels of infants who learned in a subsequent session differed as a function of soothability. Additionally, vagal levels during contingency disruption were significantly higher among infants in this group who were more soothable as opposed to those who were less soothable. The results suggest that contingency learning and disruption is associated with stable vagal tone in the majority of infants, but that individual differences in attention processes and state associated with vagal tone may be most readily observed during the disruption phase. © 2015 Wiley Periodicals, Inc . Dev Psychobiol 58: 366–381, 2016.